An Assessment of Microbiological Quality of Some Commercially Packed and Fresh Fruit Juice Available in Dhaka City: A Comparative Study - Rahman, Tasmina; Hasan, Sabrina; Noor, Rashed (Stamford Journal of Microbiology, 2011)
Fruit juices are regarded as the most preferred non-alcoholic beverage worldwide to all age groups. In general, microbial growth in fruit juice is restricted by using preservatives and also through other environmental factors during production. Still, the presence of some indicator organisms in fruit juice is responsible for causing food-borne diseases and even death. So, from public health point of view, it is quite important to know the microbiological quality of the fruit juices available in the market. Primary objective of this study was to assess the microbial quality of fresh and commercially packed available juices collected from different locations of Dhaka city. A total of six fresh juice and nine commercially packed juice samples were collected. Standard culture techniques were followed to assess total viable count (TVC), total staphylococcal count (TSC), total Bacillus count (TBC) and total fungal count (TFC) on different culture media. The TVC varied from the range of 102 to 105 cfu/ml with the highest of 2.4 x 105 cfu/ml. A large number of staphylococci and Bacillus was also found from several samples. Total coliform and fecal coliform was found in six and five (out of fifteen) samples, respectively. Among total coliforms, Klebsiella, Enterobacter along with E. coli were detected. From all the assessment it was determined that the microbial quality of commercially packed juice was fairer than that of fresh juice collected from local market. DOI: http://dx.doi.org/10.3329/sjm.v1i1.9097 Stamford Journal of Microbiology, Vol.1(1), July 2011, p.13-18